Effect of meaning on apraxic finger imitation deficits. (February 2016) - Achilles, E.I.S.; Fink, G.R.; Fischer, M.H.; Dovern, A.; Held, A.; Timpert, D.C.; Schroeter, C.; Schuetz, K.; Kloetzsch, C.; Weiss, P.H.
Abstract: Apraxia typically results from left-hemispheric (LH), but also from right-hemispheric (RH) stroke, and often impairs gesture imitation. Especially in LH stroke, it is important to differentiate apraxia-induced gesture imitation deficits from those due to co-morbid aphasia and associated semantic deficits, possibly influencing the imitation of meaningful (MF) gestures. To explore this issue, we first investigated if the 10 supposedly meaningless (ML) gestures of a widely used finger imitation test really carry no meaning, or if the test also contains MF gestures, by asking healthy subjects ( n =45) to classify these gestures as MF or ML. Most healthy subjects (98%) classified three of the 10 gestures as clearly MF. Only two gestures were considered predominantly ML. We next assessed how imitation in stroke patients (255 LH, 113 RH stroke) is influenced by gesture meaning and how aphasia influences imitation of LH stroke patients ( n =208). All patients and especially patients with imitation deficits (17% of LH, 27% of RH stroke patients) imitated MF gestures significantly better than ML gestures. Importantly, meaningfulness-scores of all 10 gestures significantly predicted imitation scores of patients with imitation deficits. Furthermore, especially in LH stroke patients with imitation deficits, the severity of aphasia significantly influenced the imitation of MF, but not ML gestures. Our findings in a large patient cohort support current cognitive models of imitation and strongly suggest that ML gestures are particularly sensitive to detect imitation deficits while minimising confounding effects of aphasia which affect the imitation of MF gestures in LH stroke patients. Highlights: Meaningfulness of gestures improves imitation scores in stroke patients. Meaningless gestures are particularly sensitive to detect apraxic imitation deficits. Dual-pathway model of gesture imitationis supported in a large stroke patient sample.